Bioprinting Embedded Non-planar Tissues (BENT) for Manufacturing Tissue Engineered Atrioventricular Valves. (9th April 2021) - Albert, Benjamin; Butcher, Jonathan
Abstract : Objective : Bioprinting has strengthened the ability to create complex materials to replace dysfunctional tissue and has been used to replicate the geometry of heart valves. Additionally, embedded printing has expanded the range of bioprintable materials. However, bioprinting microstructure of leaflets remains difficult with traditional printing methods. Extrusion printers can be programmed to move in non-planar directions to bioprint embedded non-planar tissues (BENT) by following surfaces of tissues to reproduce complex structures such as valve leaflets. Methods : Valve leaflet models were created in three diameters (12, 17, and 22mm). Briefly, the BENT method uses leaflet surfaces projected onto the X-Y plane and extruded to the final leaflet thickness (300, 600, and 900µm). These models were imported to Cura and sliced into printable paths. The files were translated to the surfaces using point matching to assign new Z-values each point. This created a 3D print file where paths follow non-planar movement so that layers form the full leaflet surface before moving to the next layer. A 12mm valve was printed in alginate (Figure 1 ) and BENT print files of three sizes were created to compare extruder changes and total layers using one, two, or three materials. Conclusions: Initial results show that non-planar printing can reduce the number of layers and extruder changes when using multiple materials to print a wide range of heart valve leaflet sizes. Future work will move to optimize printer motion for improving print time and study implications of this method on cell viability, print fidelity, and material mechanics. Results: Layers and extruder changes for leaflets printed with one, two, or three materials 22mm Valve 17mm Valve 12mm Valve Layers Extruder Changes Layers Extruder Changes Layers Extruder Changes 1. Extruder Planar 90 0 68 0 44 0 Non-Planar 9 0 6 0 3 0 2. Extruders Planar 90 80 68 62 46 29 Non-Planar 9 1 6 1 3 1 3. Extruders Planar 90 160 68 124 45 58 Non-Planar 9 2 6 2 3 2